2016
DOI: 10.1111/gfs.12246
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal nitrogen effects on nutritive value in binary mixtures of tall fescue and bermudagrass

Abstract: The addition of cool-season, tall fescue [Lolium arundinaceum (Schreb.) Darbysh.], to warm-season, bermudagrass [Cynodon dactylon (L.) Pers.], pastures can improve forage productivity and nutritive value. Effects of four binary mixtures consisting of cv. Flecha (incompletely summer dormant) and cv. Jesup (summer active) tall fescue overseeded into established stands of cv. Russell and cv. Tifton 44 bermudagrass and three seasonal N treatments were evaluated on dry-matter (DM) yield, crude protein (CP), in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…Overall, the nutritive value of ATF was greater with the presence of alfalfa than in tall fescue monocultures (Nave et al, 2014). According to a study conducted by Read, Lang, and Aiken (2017), tall fescue pastures that were fertilized with 150 lb N acre −1 had a range of 7 to 14% CP, which is still, in most instances, lower than the CP values found in this study. The results suggest that the addition of alfalfa to tall fescue mixtures generates an overall increase in nutritive value.…”
Section: Forage Nutritive Valuecontrasting
confidence: 74%
“…Overall, the nutritive value of ATF was greater with the presence of alfalfa than in tall fescue monocultures (Nave et al, 2014). According to a study conducted by Read, Lang, and Aiken (2017), tall fescue pastures that were fertilized with 150 lb N acre −1 had a range of 7 to 14% CP, which is still, in most instances, lower than the CP values found in this study. The results suggest that the addition of alfalfa to tall fescue mixtures generates an overall increase in nutritive value.…”
Section: Forage Nutritive Valuecontrasting
confidence: 74%
“…According to these authors, the grasses intercropped showed phenotypic plasticity, that is, the plants changed their growth pattern due to the competition for abiotic resources (e.g., light). Consequently, this caused a reduction in the stem diameter, thus decreasing the allocation of photosyn-thesis products and energy towards the deposition of structural carbohydrates, such as cellulose and lignin polymers, which could potentially enhance the nutritive value of intercropped grasses [47,48].…”
Section: Fm and Chemical Composition Of The Silagementioning
confidence: 99%
“…The information reported in the literature regarding mixed canopies containing perennial C 3 and C 4 grass species comes from studies conducted in areas with the Cfa climate. Some previous studies have demonstrated that the success of this type of mixed canopy depends on two factors: the coolseason perennial grass should be tolerant to heat, drought, and low soil fertility (Pitman, 1999;Read, Lang, & Aiken, 2016) and should be symbiotically associated with endophytic fungi (Franzluebbers et al, 2013) because the endophyte confers greater resistance against biotic and abiotic stresses (Bouton, Gates, Belesky, & Owsley, 1993;Malinowski & Belesky, 2000). However, such symbiotic associations between a plant and fungus can lead to the production of secondary metabolites by the endophyte, such as ergovaline, which can lead to losses in animal performance (Hoveland, 1993).…”
Section: Introductionmentioning
confidence: 99%